Eye movement instructions modulate motion illusion and body sway with Op Art - Kapoula, Zoï; Lang, Alexandre; Vernet, Marine; Locher, Paul (Frontiers in Human Neuroscience, 2015)
Op Art generates illusory visual motion. It has been proposed that eye movements participate in such illusion. This study examined the effect of eye movement instructions (fixation versus free exploration) on the sensation of motion as well as the body sway of subjects viewing Op Art paintings. Twenty-eight healthy adults in orthostatic stance were successively exposed to three visual stimuli consisting of one figure representing a cross (baseline condition) and two Op Art paintings providing sense of motion in depth – Bridget Riley’s Movements in Squares and Akiyoshi Kitaoka’s Rollers. Before their exposure to the Op Art images, participants were instructed either to fixate at the center of the image (fixation condition) or to explore the artwork (free viewing condition). Posture was measured for 30 s per condition using a body fixed sensor (accelerometer). The major finding of this study is that the two Op Art paintings induced a larger antero-posterior body sway both in terms of speed and displacement and an increased motion illusion in the free viewing condition as compared to the fixation condition. For body sway, this effect was significant for the Riley painting, while for motion illusion this effect was significant for Kitaoka’s image. These results are attributed to macro-saccades presumably occurring under free viewing instructions, and most likely to the small vergence drifts during fixations following the saccades; such movements in interaction with visual properties of each image would, increase either the illusory motion sensation or the antero-posterior body sway.